BAURAN PROMOSI PAKET WISATA HALAL KOREA SELATAN PADACHERIA HALAL HOLIDAY TRAVEL - Mayza, Karina; Gulfira, Poeti Nazura (Journal of Indonesian Tourism and Policy Studies, 2017)
The focus of this study is about Promotional Mix "Halal Tour Packages of South Korea" on Cheria Halal Holiday. The purpose of this study is to know promotional mix activities on Cheria Halal Holiday in marketing "Halal Tour Packages of South Korea" and their obstacles. South Korea became one of the countries that began to develop halal tourism. This is an opportunity for Cheria Halal Holiday to promote South Korea's halal tour packages. In this study using Qualitative Descriptive method by interviewing with resource person and direct observation at Cheria Halal Holiday office. The concepts used in writing are Tourism, Halal Tourism, Tourism Promotion, and Tourism Promotion Mix. Promotion mix is very important to support the sales activities of Cheria Halal Holiday’s packages, for example Halal Tour Packages of South Korea. Based on the observations, Cheria Halal Holiday has done the promotion mix accordance with the concept. Cheria is considered to be able to market South Korea halal tour package products well although still encountered some obstacles such as expensive price. However this does not diminish the interest of the community because of the halal tourist services that become the hallmarks of this product.